Usefulness of Preoperative Surgical Simulation with Three-Dimensional Fusion Images for Resection of Cerebral Cavernous Malformations Near Broca's Area. (14th April 2014) - Takahashi, Satoshi; Tanizaki, Yoshio; Akaji, Kazunori; Kano, Tadashige; Hiraga, Kenji; Mihara, Ban
Abstract : Treating subcortical brain lesions in or near eloquent areas is challenging not only because lesions must be resected while preserving brain tissue involved in essential functions, but also because lesions often cannot be easily identified from the surface of the brain. Here, we report 2 cases of cerebral cavernous malformations near Broca's area. In both cases, lesions were surgically removed by utilizing three-dimensional fusion images created using preoperative magnetic resonance imaging and computed tomography data. Excisions were completed without any worsening of speech function, and the use of presurgical simulations was found to be useful in the design and execution of the actual operations. The technique described in this report serves as a useful tool in simulating surgical strategies by using brain gyri and sulci as surgical landmarks. Furthermore, in contrast to other intraoperative techniques, this method can aid in shortening the duration of surgery and can help limit damage to eloquent areas of the brain.